Onset Reduction and Stabilization of Cocontinuous Morphology in Immiscible Polymer Blends by Snowmanlike Janus Nanoparticles - You, Wei (Langmuir : the ACS journal of surfaces and colloids, 2018)
Interfacial jamming of monolayer nanoparticles is often required to kinetically arrest the cocontinuous morphology, which is not in favor of achieving high efficiency at low particle contents. In this paper, we find that the shape asymmetry of the snowmanlike Janus particles (JPs) has significant influence on the cocontinuous morphology of polymer blends under the melt-mixing process. The addition of 0.9 vol % snowmanlike JPs can almost have the onset concentration of cocontinuity in immiscible blends, which is much lower than the apparent interfacial jamming concentration. In addition, JPs show superior ability to stabilize the continuous morphology during annealing at high temperatures. The interfacial activity of asymmetric JPs is due to the decrease in the radius of the jamming curvature in the interfacial region as the shape asymmetry of the snowmanlike JPs increases. This result implies a general strategy to prepare Janus nanoparticles for a highly effective interfacial modification agent at low contents, which can induce the dispersed-phase continuity and suppress the coarsening of cocontinuous morphology simultaneously